Physical and chemical characterization of urban winter-time aerosols by mobile measurements in Helsinki, Finland. (June 2017) - Pirjola, Liisa; Niemi, Jarkko V.; Saarikoski, Sanna; Aurela, Minna; Enroth, Joonas; Carbone, Samara; Saarnio, Karri; Kuuluvainen, Heino; Kousa, Anu; Rönkkö, Topi; Hillamo, Risto
Abstract: A two-week measurement campaign by a mobile laboratory van was performed in urban environments in the Helsinki metropolitan area, Finland, in winter 2012, to obtain a comprehensive view on aerosol properties and sources. The abundances and physico-chemical properties of particles varied strongly in time and space, depending on the main sources of aerosols. Four major types of winter aerosol were recognized: 1) clean background aerosol with low particle number (Ntot) and lung deposited surface area (LDSA) concentrations due to marine air flows from the Atlantic Ocean; 2) long-range transported (LRT) pollution aerosol due to air flows from eastern Europe where the particles were characterized by the high contribution of oxygenated organic aerosol (OOA) and inorganic species, particularly sulphate, but low BC contribution, and their size distribution possessed an additional accumulation mode; 3) fresh smoke plumes from residential wood combustion in suburban small houses, these particles were characterized by high biomass burning organic aerosol (BBOA) and black carbon (BC) concentrations; and 4) fresh emissions from traffic while driving on busy streets in the city centre and on the highways during morning rush hours. This aerosol was characterized by high concentration of Ntot, LDSA, small particles in the nucleation mode, as well as high hydrocarbon-like organic aerosol (HOA) and BC concentrations. In general, secondary components (OOA, NO3, NH4, and SO4 ) dominated the PM1 chemical composition during the LRT episode accounting for 70–80% of the PM1 mass, whereas fresh primary emissions (BC, HOA and BBOA) dominated the local traffic and wood burning emissions. The major individual particle types observed with electron microscopy analysis (TEM/EDX) were mainly related to residential wood combustion (K/S/C-rich, soot, other C-rich particles), traffic (soot, Si/Al-rich, Fe-rich), heavy fuel oil combustion in heat plants or ships (S with V-Ni-Fe), LRT pollutants (S/C-rich secondary particles) and sea salt (Na/Cl-rich). Tar balls from wood combustion were also observed, especially (∼5%) during the LRT pollution episode. Highlights: Four distinct sources and corresponding characteristics of aerosols were identified. Size distributions of particle number and lung deposited surface area were measured. OOA and inorganics dominated chemical composition during long-range transport episode. BC, HOA and BBOA dominated local traffic and wood burning emissions. High amounts of K/S/C-rich and soot particles were detected in small house areas.